2008
DOI: 10.1158/1535-7163.mct-08-0549
|View full text |Cite
|
Sign up to set email alerts
|

N-(4-Hydroxyphenyl)retinamide increases dihydroceramide and synergizes with dimethylsphingosine to enhance cancer cell killing

Abstract: Fenretinide [N-(4-hydroxyphenyl)retinamide (4-HPR)] is cytotoxic in many cancer cell types. Studies have shown that elevation of ceramide species plays a role in 4-HPR cytotoxicity. To determine 4-HPR activity in a multidrug-resistant cancer cell line as well as to study ceramide metabolism, MCF-7/AdrR cells (redesignated NCI/ADR-RES) were treated with 4-HPR and sphingolipids were analyzed. TLC analysis of cells radiolabeled with [ 3 H]palmitic acid showed that 4-HPR elicited a doseresponsive increase in radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
108
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 49 publications
7
108
0
Order By: Relevance
“…Ceramide production in HPR-treated tumor cells is somehow peculiar, because it has been suggested that the most relevant mechanism for HPR-induced ceramide generation might be the de novo biosynthesis (HPR is indeed a potent activator of serine palmitoyltransferase and dihydroceramide synthases, the key enzymes in the early steps of ceramide biosynthesis), whereas for many other antitumor drugs sphingomyelin hydrolysis due to the activation of sphingomyelinases is the main source of pro-apoptotic ceramide. Moreover, it has been demonstrated that dihydroceramide, rather than ceramide, accumulates in HPR-treated tumor cells, due to the inhibitory effect of this retinoid on dihydroceramide desaturase (22,24,37). Indeed we recently showed by electrospray ionization-MS analysis that dihydroceramide and not ceramide is increased upon treatment of A2780 cells with HPR (36).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Ceramide production in HPR-treated tumor cells is somehow peculiar, because it has been suggested that the most relevant mechanism for HPR-induced ceramide generation might be the de novo biosynthesis (HPR is indeed a potent activator of serine palmitoyltransferase and dihydroceramide synthases, the key enzymes in the early steps of ceramide biosynthesis), whereas for many other antitumor drugs sphingomyelin hydrolysis due to the activation of sphingomyelinases is the main source of pro-apoptotic ceramide. Moreover, it has been demonstrated that dihydroceramide, rather than ceramide, accumulates in HPR-treated tumor cells, due to the inhibitory effect of this retinoid on dihydroceramide desaturase (22,24,37). Indeed we recently showed by electrospray ionization-MS analysis that dihydroceramide and not ceramide is increased upon treatment of A2780 cells with HPR (36).…”
Section: Discussionmentioning
confidence: 90%
“…Indeed we recently showed by electrospray ionization-MS analysis that dihydroceramide and not ceramide is increased upon treatment of A2780 cells with HPR (36). In addition, recent observations suggest that HPR cytotoxicity might at least in part due to the elevation of cellular sphinganine levels (24). Independently from the mechanism underlying the production of cytotoxic (dihydro)ceramide upon chemotherapeutic treatments, it has been suggested that the acquired resistance to chemotherapeutic drugs in tumors and tumor cell lines can be ascribed to alterations in sphingolipid metabolism leading to a reduced potential for dihydroceramide formation or an increased clearance of dihydroceramide.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…SphK1 was significantly elevated in azoxymethane-induced murine colon cancer tissues, SphK1 knockout mice subjected to azoxymethane had significantly less aberrant formation of crypt foci and cancer development (7). Moreover, SphK1 inhibitor or shRNA enhanced the cytotoxicity and chemosensitivity of colon cancer cells (8,9). Studies also showed that the expression of SphK1 was required for the proliferation of small intestinal tumor cell and SphK1 was able to promote intestinal adenoma progression (10).…”
Section: Introductionmentioning
confidence: 99%